Assessing the potential of ICT to increase land and labour productivity in agriculture: Global and regional perspectives - Rajkhowa, Pallavi; Baumuller, Heike (Journal of Agricultural Economics, 2024)
Increasing agricultural productivity in low- and middle-income countries (LMICs) is an important channel for reducing poverty and food insecurity. Information and communication technologies (ICT) have the potential to boost agricultural productivity by lowering transaction costs and enhancing access to information. Even though there are several micro-level studies analysing the effects of ICT on agricultural productivity, there is scant research addressing the role of ICT in agricultural productivity at the global and regional levels. Using data from 86 countries for the period 2000 to 2019 and utilising a fixed effect panel regression with a feasible generalised least square approach, we find that globally there is a positive and significant association between ICT uptake and both land and labour productivity in agriculture. In each case, however, the magnitude of the effect is much smaller than other important determinants, such as human capital, access to inputs or environmental factors. At the regional level, the relationship between ICT uptake and land productivity is not significant in Africa and Asia, while we find a significant effect on labour productivity. This finding indicates that while ICT can provide valuable information and tools for land management, the effect on land productivity might be less immediate in these regions. Finally, we revisit the question of whether ICT expansion increases agricultural productivity gaps between high-income nations and LMICs. In contrast to previous research, this study does not find significant differences in the effects of ICT on land and labour productivity between higher-income and lower-income countries.
Keywords: Agricultural Productivity; Cross-Country Analysis; ICT; Infrastructure; Human Capital